Pengaruh Usia terhadap Cervical Intraepithelial Neoplasia (CIN) pada Wanita dengan Infeksi Saluran Reproduksi Berbasis Pemeriksaan Papsmear - Anggraini, Dewi Okta; Dirgahayu, Paramasari; Wasita, Brian (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Cervical Intraepithelial Neoplasia (CIN) is a dysplasia of cervical squamous cells posibbly turn into cervical cancer if not treated immediately. The established cause of CIN is Human Papillomavirus (HPV). Several studies showed correlation between Reproductive Tract Infection (RTI) with CIN. But, it is still controversial. Age is one of predicted factor which can influence CIN. Through some mechanisms, age can change the cervical cells. Methods: This study was cross-sectional approach. Samples were taken from medical record, papsmearâs form result and papsmear preparation in the Pathology Anatomy Laboratory, Faculty of Medicine, Sebelas Maret University from 2009-2012. Total of 410 samples were divided into two groups: control and case group. Control group contain sample without RTI while case group contain sample with RTI. Each group consisted of 205 women who subsequently divided into two subgroup, aged <40 years and â¥ 40 years. In this study, HPV infection is uncontrolled. Data were taken including name, age, clinical symptoms, ISR and CIN. These data are analyzed using Fisher test from SPSS version 19 for windows. Results: Total CIN were found: 5 samples (<40 years) and 3 samples (â¥40 years) from positive RTI; 20 samples (<40 years) and 53 samples (â¥40 years) from negative RTI. Fisher test results showed that age has correlation with CIN (p=0,001) and there is a significant difference risk between the age distribution with CIN [RD= -12.3%, 95%CI=(-19.8)-(-4798)]. In the negative RTI, there is a significant risk sample aged <40 years and aged â¥40 years to get CIN [RD= -21.28%, 95% CI= (-33.91)- (-8.655)]. RTI does not have correlation with CIN (p = 0.06) Conclusion: Without HPV controlled, age distribution (<40 years and â¥40 years) has an influence to the occurence of CIN and there is no correlation between RTI with CIN. Key words: Age, Cervical Intraepithelial Neoplasia (CIN), Reproduction Tract Infection (RTI)